(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This study investigates the advancements in polymer pipe welding technologies, comparing traditional methods such as butt fusion, electrofusion, and socket fusion with innovative robotic-assisted welding techniques. It evaluates the impact of advanced materials, including carbon fiber-reinforced polymers, on the strength and durability of welded joints. The research highlights the scientific novelty of integrating automation and new materials into welding processes, emphasizing the potential for cost reduction and increased joint reliability. Predictive models are developed to forecast the lifespan of welded joints under various operational conditions, providing valuable insights for decision-making in pipeline construction and maintenance.